Метрологическое обеспечение геофизических исследований скважин: справочник - Блюменцев А. М. Аркадий Михайлович; Абросимов М. Г. Михаил Георгиевич; Козыряцкий Н. Г. Николай Григорьевич; Мельчук Б. Ю. Борис Юрьевич (Москва, Изд-во ВНИИгеосистем, 2011)
Авт. указаны на обороте тит. л.